Activating Factors Of The Community Based Education Network By Region Type For Improving Young Children’s Character - Heejeon Suh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to examine the differences of current states and analyze the importance-performance of activating factors in the community based education network (CEN) for improving young children's character by region type. The subjects in this study were 344 teachers of kindergartens and child care centers located at 13 provinces in Korea. The questionnaire was composed of the perception of the purpose of young children’s character education through the CEN, current states of community connected & collaborative education activities, and the importance and performance of the activating factors of CEN. The results of examining current states of CEN showed that In terms of 'utilization of human resources in the community’ and 'use of institutions and facilities', the rural town found to be lower than big cities and small & medium sized cities. Importance-Performance Analysis results according to region types show that big cities and small and medium-sized cities need intensive improvement efforts in aspects of rich human and material resources of the community and professional education staff in community organizations. In rural towns, it is found that 'leadership' are insufficient. These results can be used as basic data for cultivating the character of young children and the direction to activate the CEN.